PENGARUH SWEDISH MASSAGE TERHADAP KUALITAS TIDUR LANSIA - Ance Nopentri Pratama; Arneliwati " "; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract   The purpose of this research was to determine the influence Swedish massage therapy to quality of sleep for elderly. The design of this research was “Pre experimental design one group only” designed by “One group pre test-post test”. The research has been conducted in the Panti Sosial Tresna Werdha Khusnul Khotimah at Pekanbaru. The sample were 34 respondents who fit the inclusion criteria and chosen by purposive sampling technique. Measuring instrument that using questionnaire of Pittsburgh Sleep Quality Index (PSQI). Implementation of Swedish massage theraphy has been did in thirty minutes and during three days in a row. The analysis has been used univariate and bivariate by using Wilcoxon test. The result showed that there was a significant variance of sleep quality in elderly which has given Swedish massage with p value (0.000) < α (0.05). It can be concluded that the Swedish massage therapy was influence to improve the quality of sleep for elderly. Based on this research the Swedish massage therapy can be used as a non pharmacological therapy to increase sleep quality of elderly. Keyword: Elderly, Swedish massage, quality of sleep